Inventario de fincas y haciendas con fines de uso turístico para el fomento del concepto de paisaje cultural de cacao en la zona centro-norte de Manabí - García Espinel, Alex Darío (2022)
The objective of this research was to develop an inventory of farms and haciendas for tourist use purposes to promote the concept of cultural landscape of cocoa in the north-central area of Manabí; the research was qualitative with an exploratory descriptive approach. The methodological process consisted of four phases: in the first instance, a general diagnosis of the province was made and a characterization of the components was carried out for the identification of cultural landscapes of the cantons of the central zone, resulting in the identification of territories with special tourist interest; Thanks to the references obtained by local authorities and the subsequent field work carried out, interviews and a SWOT matrix were applied for this stage; in the second phase, the services and landscape diversity provided by the farms and haciendas of the cantons of the study area were identified; the tool that was used was an interview questionnaire for authorities and owners through Zoom Meetings; In the third phase, an analysis was carried out about the cocoa culture and it was limited through the matrix of potentialities that the farms have great natural and cultural diversity that must be managed; Finally, in the fourth phase, the inventory model of farms and ranches was structured to promote the concept of cultural landscape. The purpose of this inventory is to identify cocoa-producing farms with the potential to spread the significance of cultural landscapes and create new products that generate interest.